Internal Control Systems and Financial Performance of SACCOs in Kabale Municipality. - Kyomugisha, Loyce (Kabale University, 2024)
The intention of this research was to examine how internal control systems have influenced SACCO’s financial performance in Kabale Municipality's. The research project concentrated on three predictor variables: Control Environment, Risk Assessment, and Control Activities. The outcome variable was Financial Performance. The study used a cross-sectional survey design that combined quantitative and qualitative research methods, providing generalizable and readily replicable data from the former with detailed insights from the latter. A total of 97 respondents participated. These were selected using simple random sampling and contacted by questionnaires and interview guide. Data was analysed using descriptive statistics (means and standard deviation) and multiple regression analysis. The study revealed a strong correlation (r = 0.653) between the control environment and financial performance of SACCOs, the correlation between control Activities and financial performance (0.699), and r=0.613 for Risk Assessment and Financial performance of SACCOs in Kabale municipality. The results from the study show a positive Significance of the predictors (Control Environment, Control activities, and Risk Assessment on the Financial performance of SACCOs in Kabale municipality. It was established that internal control systems, including risk assessment, control activities, and control environments, had a major impact on SACCO's financial performance in Kabale Municipality. As a result, SACCOs should carefully adhere to internal control systems for improved financial performance. The study recommends that there is need for putting more effort on Control Environment, Control Activities, and Risk Assessment in order to maintain a positive Financial Performance of SACCOs in Kabale Municipality, also, further studies on other factors affecting Financial Performance of SACCOs in Kabale Municipality as well as the contribution of other internal control systems such as Monitoring, reporting and reconciliations needs to be done in order to review their effect on Performance of SACCOs in Kabale Municipality.